ソウセツ ナンキョク ニ オケル ユウキ エンソ カゴウブツ ノ ケンキュウ - 日高, 秀夫; ヒダカ, ヒデオ; 立川, 涼; タツカワ, リョウ; Hidaka, Hideo; Tatsukawa, Ryo (1981)
P(論文) 南極地域における有機塩素化合物の研究を概観するとともに, 第22次隊の調査計画を紹介した。1966年以来, 有機塩素汚染関係の原著論文は18編見つかったが, 雪の分析が3論文ある他は, すべて野生生物の残留分析である。そのほとんどがアメリカ, イギリス, ニュージーランドの観測隊によって行われたもので, 昭和基地周辺ではアデリーペンギンとウェッデルアザラシ, 各1個体ずつのPCB分析値しかない。第22次隊では, 大気, 雪, 海水, 底質, 土壌, 生物など, あらゆる環境分析試料を採取し, 南極地域における汚染の実態を明らかにするとともに, 汚染物質のグローバルな移動拡散, 食物連鎖系における動態なども解明したい。 Papers published in 1966-1979 on the environmental pollution by chlorinated hydrocarbons in the Antarctic are reviewed and the investigation plan on the environmental pollution of the 22th Japanese Antarctic Research Expedition (JARE-22) 1980-1982 is introduced. The relevant original papers of eighteen have been published since 1966,which were pertinent to residual analyses of wildlife in the Antarctic, except three papers on analyses of the Antarctic snow. The studies so far were undertaken mostly by the expeditions of the United States, United Kingdom and New Zealand. There is only one paper on Syowa Station, which dealt with PCB's in an Adelie penguin and a Weddell seal. JARE-22 will attempt to collect the environmental materials around Syowa Station in the Antarctic, including air, snow, sea water, sediment, soil, plankton, fishes, penguins and seals. Their chlorinated hydrocarbon analysis will be expected to make clear the environmental concentrations, global distribution and transport, and pollution dynamics in the Antarctic food webs. departmental bulletin paper